2016
DOI: 10.1007/978-981-10-1498-7_11
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs Regulating Cancer Signaling Network

Abstract: The cellular signaling network plays a fundamental role during development and disease, especially cancer progression. By deregulating signaling pathways, cancer cells acquire hallmarks of the disease including uncontrolled proliferation, evasion from cell death, activation of angiogenesis, invasion, and metastasis. Noncoding RNAs make substantial contributions to regulating signal transduction in cancer, thereby promoting or suppressing different biological processes during tumorigenesis. This chapter provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…It is well known that miRNAs can regulate downstream signal pathways, activating or blocking downstream effector molecular signal transduction, through affecting the key genes expression in cancer ( 28 , 29 ). With the deepening of research in recent years, miRNA has the ability to participate in cell proliferation, apoptosis, migration, invasion and other physiological processes, which have been confirmed ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that miRNAs can regulate downstream signal pathways, activating or blocking downstream effector molecular signal transduction, through affecting the key genes expression in cancer ( 28 , 29 ). With the deepening of research in recent years, miRNA has the ability to participate in cell proliferation, apoptosis, migration, invasion and other physiological processes, which have been confirmed ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs can positively or negatively regulate signaling pathways, promoting or preventing signal transmission to downstream effectors. Multiple studies have demonstrated that miRNAs play key functions in tumorigenesis by regulating tumor suppressors or oncogenes (108,109). Over the past decade, research on the pathogenesis of BC has led to the discovery of a number of signaling pathways and corresponding therapeutic targets involved in BC, such as transforming growth factor β (110,111), phosphoinositide-3-kinase (PI3K), v-akt murine thymoma viral oncogene homolog (AKT), mechanistic target of rapamycin (mTOR) (112)(113)(114), Ras/mitogen-activated protein kinase (MAPK) (115,116), nuclear factor (NF)-κB (117)(118)(119)(120), Notch (121)(122)(123), Wnt/β (124,125), HER2 (126), vascular endothelial growth factor (VEGF) (127,128), epidermal growth factor receptor (EGFR) (129,130), cyclin-dependent kinase 4/6 (CDK4/6) (131), poly(adenosine diphosphate-ribose) polymerase (PARP) (132,133) and programmed death-1 (PD-1) (134).…”
Section: Mirnas and Various Signaling Pathways And Therapeutic Target...mentioning
confidence: 99%
“…Multigene regulatory features of these small RNA molecules allow them to change signaling pathways, facilitate or block signal transmission to downstream effectors in various ways. MiRNAs can regulate key signaling pathways positively or negatively, therefore they can affect tumorigenesis (Hu, Markowitz, & Wang, ; Zarredar et al, ). Various signaling pathways have been elucidated in the cell, most of them are important to a cascade of biological events and gene expression.…”
Section: Introductionmentioning
confidence: 99%